Ultra-high precision white dwarf asteroseismology. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Giammichele, Noemi; Charpinet, Stéphane; Fontaine, Gilles; Brassard, Pierre; Zong, Weikai
Abstract: We present a brief progress report in our quest for deriving seismic models of pulsating white dwarfs that can account simultaneously for all the observed periods at the precision of the observations. We point out that this is possible from a pratical point of view only if parametrized models are used to complement evolutionary models. We adopt a double optimization procedure that insures that the best possible model in parameter space is found objectively and automatically. Our ultimate goal is to be able to account for the exquisite period data gathered with Kepler and Kepler-2 on key pulsating white dwarfs of both the DA (ZZ Ceti) and DB (V777 Her) type.